Fluid flow studies of the F-5E and F-16 inlet ducts - Imran Halimi Ibrahim (2009)
The intake represents the front of a complex aerodynamic system. The shape of the intake diffuser follows the contours of the aircraft for external aerodynamic reasons. However the meandering shape can result in unwanted secondary flow or swirl build up at the Aerodynamic Interface Plane (AIP), resulting in engine flutter and stall. Using the Finite Element Method (FEM) Partial Differential Equations (PDE) calculator COMSOL, the compressible flow equations were obtained by the coupling of the continuity and momentum equations in the k-ε turbulence model and the energy equation conduction and convections model. The standard validation and verification techniques employed in the computational analysis were conducted in the study of F-5E and F-16 aerodynamic intakes. The results were validated using experimental results of the circular S-duct. Static pressure contours of the S-duct were compared at the azimuthal angles 0ο, 90ο and 180ο with reasonable agreement. The Grid Convergence Index (GCI) study done on the circular S-duct, F-5E and F-16 intakes using the pressure recovery as variable.